“Us” and “them”: collective identity-building of far-right movements in Chemnitz and “Querdenken” - Schmidt-Kleinert, Anja (Frontiers in Sociology, 2025)
Far-right actors successfully mobilized supporters for protests in the city of Chemnitz, Germany, in the summer of 2018, triggered by the fatal stabbing of a German national and the subsequent arrest of two asylum seekers. At first glance, they applied familiar enemy constructions in their online communication on the event. However, a more detailed analysis showed that these “enemies” were not targeted randomly. In this paper, I address the question of how the collective far-right actors in two German case studies—Chemnitz and “Querdenken”—framed their online communication on Facebook to foster the process of the respective social movement's collective identity-building. In particular, I focus on the role that the construction of out-groups, or “enemies” plays for their collective identity-construction. I apply frame analysis. The findings show that diagnostic master frames of “enemy” outgroups and “crisis” prove essential components; besides, diagnostic frames are more or less the only frame dimension identified. As master frames they hint to a collectively shared knowledge across the two discursive events.